STRATEGI PEMBELAJARAN GURU DALAM MEMBENTUK KEMANDIRIAN ANAK TUNAGRAHITA di SEKOLAH LUAR BIASA NEGERI 1 KOTA PADANG - Wahyuni, Meta; Kasih, Fitria; Yulastri, Weni (Bimbingan dan Konseling, 2014)
A child have special requirement to frequently assumed to differ from normal , they seen as not powered and require to feel pity . Not only that, they tend to to get treatment of discriminative, education service to child with functional growth resistance stand in need of serious than teacher in social interaction. All teacher are often given on to the problem of giving of special service. Hence, this research aim to describe to study of teacher strategy in forming child independence of tunagrahita in Extraordinary School 1 Padang. Type Research which used in this research is qualitative research with research location SLB Country 1 Field town. As informan in this research, the reasearcher amount are 3 people learn SLB, including Headmaster. Documentation study of this research are technique, observation, and interview. Accuracy of data tested by using sampling snowball, of gathered to be data to be analysed which consist of data collecting, result of interview, and observation to be made conclusion. The result of this research indicate that : seen that school have conducted classification of child of tunagrahita with two way. First, they can train, educated, and take care. Secondly it can seen by weight, normal and low. That classification also strenghtened with result of inspection of IQ which have been conducted by doctor. Teacher and other school also used variety strategy such as; strategy study of cooperative, competitive and individually with aim to increase achievement, recall, grow motivation learn, improving child socialization of tunagrahita with other normal child. Some note found development of seldevelopment of every Saturday has strategic time to develop potency had by educative participant. Besides researcher also find made by handicrafts educative by participant. Its quality is equal to residing in marketing, so that, it can be concluded that the skill have economic valuable. The researcher hope,Expected of school can continued to develop variety method which give appropriate education for the child have special requirement.